Optimization of ferrofluid motion on solid substrate and its application to micro-mirror device - Yu, Seonuk; Kim, Dongil; Cho, Il-Joo; Yun, Kwang-Seok (IOP PUBLISHING LTD, 2015)
This paper presents and demonstrates the optimization of an oil-based ferrofluid droplet on a solid surface and its application to a micro-mirror device with a fast switching time. The motion of the ferrofluid droplet on a hydrophilic surface was examined at various surfactant concentrations for both rotational and linear reciprocating actuations. A maximum moving speed of 0.733m/s was measured at a poly(vinyl alcohol) (PVA) concentration of 0.1wt% during the rotational motion of the ferrofluid droplet. In addition, a fast reciprocating motion was successfully demonstrated during the linear operation experiment without droplet separation or surface contamination. A maximum acceleration and deceleration of 28m/s(2) was measured at a PVA concentration of 0.1 wt %. As an application of the fast motion of the ferrofluid, a current-driven micro-mirror was proposed and experimentally demonstrated. Switching times of 25 and 18ms were measured for the closing and opening phases of the mirror, respectively. (C) 2015 The Japan Society of Applied Physics
Keywords: ELECTROWETTING-BASED ACTUATION; LIQUID DROPLETS; DEFORMABLE MIRROR; MAGNETIC FLUIDS; SURFACE-TENSION; VOLTAGE; LENS